Mathematical Modelling of Soil Hydraulic Properties and Numerical Analyses of Moisture Dynamic - SARIYEV, ALHAN; POLAT, VEYSEL; MUJDECI, METIN; YUSUFOVA, MELAHAT; AKCA, ERHAN (Asian Journal of Chemistry, 2010)
For determination of the state of soil water, which is a function of time and depth in soil system, water flux in soil should be modelled. Therefore, designating a suitable model yielding the interactions between soil moisture content (W), water potential (P) and hydraulic conductivity (K) is the prerequisite. Some samples collected from the some physical and chemical properties. Hydraulic conductivity and soil moisture characteristics of the studied soil were determined by utilizing SIMONA (SIMONA, is basic model describing physical and bio physical processes in agro ecosystem) software most suitable model known at present. For the solution of soil moisture dynamic equation finite differences method was used. The soil water dynamics values obtained from the model and laboratory measurements were also correlated in the studies.